Velutinus, a novel genus in Patellariopsidaceae from medicinal plants in Sichuan Province, China - Wu, Na; Chethana, K.w. Thilini; Liu, Jian-Kui (Phytotaxa, 2024)
Velutinus sichuanensis gen. et sp. nov. was collected from dead branches of the medicinal plant Loropetalum chinense var. rubrum (Hamamelidaceae) in Sichuan Province, China. The genus Velutinus is characterized by having cylindrical, straight or slightly curved, septate, hyaline conidiophores, holoblastic, polyblastic conidiogenous cells, and thick-walled, dark brown, septate, spherical conidia, sometimes with conspicuous appendages. Molecular phylogenetic analyses based on the combined ITS and LSU sequences data showed that Velutinus forms a distinct lineage in Patellariopsidaceae, Helotiales, Leotiomycetes. The new genus, Velutinus is introduced to accommodate V. sichuanensis based on morphological characteristics and multi-gene phylogenetic analyses. Detailed descriptions and illustrations of the new taxa are provided.